From Individual to Corporate Criminal Liability : An Islamic Criminal Law Analysis of Anamnesis Inaccuracy and Misdiagnosis in Telemedicine - Handoyo Prasetyo; Bambang Waluyo; Subakdi Subakdi; Edward Benedictus Roring; Bakhytbek Begaliyev A. (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
The advancement of digital health technology through telemedicine offers significant opportunities but also raises serious legal challenges , particularly concerning inaccurate anamnesis and misdiagnosis that May cause substantial harm to patients . Existing legal scholarship and regulatory frameworks in Indonesia predominantly focus on individual liability of medical practitioners , while the criminal liability of telemedicine corporations for systemic failures remains conceptually underdeveloped . This gap leaves corporate accountability insufficiently addressed in cases where patient harm arises from platform- based medical services . This study aims to analyze the forms of corporate criminal liability of telemedicine providers in cases of inaccurate anamnesis and misdiagnosis resulting in patient harm and to examine how Islamic criminal law approaches such liability . Using normative legal research with statutory and conceptual approaches , this study analysis relevant regulations , legal doctrines , and principles of Islamic criminal law . The findings indicate that existing regulations assign responsibility for service quality to healthcare facilities but do not explicitly regulate corporate criminal liability for telemedicine providers . This study advances a theoretical argument that misdiagnosis in telemedicine should be reconceptualized as a form of corporate criminal responsibility rather than merely a professional individual negligence . From the perspective of Islamic criminal law , this article offers a conceptual contribution by applying the doctrine of shakhsiyah iʿtibāriyyah to telemedicine corporations , with diyāt and taʿzīr proposed as appropriate accountability mechanisms . Strengthening the regulatory framework to explicitly recognize corporate criminal liability is essential to enhance patient protection and ensure justice in digital health sector.